An architecture to build high performance infrastructures on cloud computing for telecommunications organizations - Omar Antonio Hernández Duany; Caridad Anías Calderón; Roberto Sepúlveda Lima; Fernando de la Nuez García; Cornelio Yáñez-Márquez (Universitas Ahmad Dahlan, 2025)
Nowadays, many small and medium organizations of the telecommunication sector must solve intrinsic heterogeneous problems in their own environments that have been associated with high computational complexities of their algorithms. These class of problems require to use high performance computing (HPC) infrastructures for their executions. Therefore, these must be accelerated to reduce significantly the execution times, included many problems that should be solved in real time: like the processing of multiples video streams, the pattern recognition in big volumes of data, the traffic analysis in cybersecurity solutions and among others. The building of HPC infrastructure permits to organize the technological platform to increase the productive and business indicators of the organizations. This paper describes an architecture as reference model and ecosystem for the building and systematic improvement of HPC infrastructures based on practical experiences from successive process of HPC infrastructure building on cloud deployment. That’s processes have been useful for the organizations permitting the integration of emergent hardware and software components launched to the international market. This landscape vision is pertinent for academics, scientifics and business organizations compelled to implement scientific and engineering applications to diverse fields that have a high impact in the society digital transformation.